A century of progress in combating yellow fever - Brès, P. L. J. (1986)
Yellow fever was responsible for several epidemics among the settlers in tropical areas of the Americas and Africa during the 17th to the 19th centuries. Scientific research into its cause and epidemiology was started at the beginning of the present century and progressed well ahead of other viral disease research. However, epidemics still occur and the worst one ever recorded was in Ethiopia in 1960-62. Epidemiological research has recently provided new findings on the ecology of the virus and the risk of epidemics. Recent breakthroughs in the molecular study of the virus should provide new tools for further progress in treatment and control of the disease. Meanwhile, the risk of urbanization of the disease, deficiencies in treatment, limitations in vector control, and erratic policies in preventive immunization present real problems.